Análise de viabilidade de um silo de grãos para pequenas e médias propriedades rurais - Scherer, Gabriel da Silva (2022)
Observing an opportunity for improvement in the agrarian sector market, company X developed a new system for the implementation of silos for storage and drying of grains, bringing the product as a proposal for building a clean, fast and cost-effective work. In this context, the study aims to evaluate the feasibility of implementing a prefabricated concrete silo for grain storage in small and medium-sized rural properties. The methodology of the work consists of a research with a quali-quantitative approach, of a basic (pure) nature, with a descriptive objective and research method with a survey with two rural landowners. The main results demonstrate customer satisfaction when using this storage system, whether for product quality, speed of execution or affordable cost, meeting and even exceeding their expectations. This research contributed mainly by presenting a new alternative to alleviate the problem of grain storage in the country, and the shortage of labor, especially in the civil construction sector. In addition, the product has an important positive aspect as it avoids wasting material on site.